How to Trick Your Opponent: A Review Article on Deceptive Actions in Interactive Sports - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (Frontiers in Psychology, 2017)
Performing deceptive actions is a wide-spread phenomenon in sports and it is of considerable practical relevance to know whether or not a fake or a disguised action decreases the opponents’ performance. Therefore, research on deceptive actions for various sport disciplines (e.g., cricket, rugby, martial arts, soccer, basketball) has been conducted. This research is scattered, both across time and scientific disciplines. Here, we aim to systematically review the empirical work on deceptive actions in interactive sports and want to give an overview about several issues investigated in the last decades. Three main topics of the detected literature were discussed here: (1) the role of expertise for the recognition of deceptive actions;, (2) the cognitive mechanisms underlying the processing of deceptive actions;, and (3) the pros and cons of in-situ research designs. NeitherNone of these themes seems to be settled and therefore, they should be considered in future research agendas.